Revisiting the Sustainable Development Goal 4 “Quality Education”: Insights, Prospects, and Recommendations - Gunawan, William Ben (Wise Education, 2025)
This paper explores the global challenges and prospects associated with the implementation of the United Nations Sustainable Development Goals (SDGs), with a focused analysis on Goal 4: Quality Education. Drawing on current data, scholarly research, and policy reports, the study identifies disparities in educational access and quality across regions, emphasizing how socio-economic, geographical, political, and digital divides impede equitable learning opportunities. A comparative analysis of four countries—Nigeria, India, Finland, and Japan—illustrates how varying governance structures, economic capacities, and cultural dynamics shape education outcomes. The study further examines the impact of global phenomena such as the COVID-19 pandemic, geopolitical tensions, energy transitions, and economic downturns on educational systems. Through this multi-scalar analysis, the paper identifies structural barriers and systemic weaknesses that hinder progress toward SDG 4, particularly in low-income and conflict-affected regions. The paper concludes by offering actionable recommendations, including intersectoral collaboration, inclusive education policy reforms, investment in digital infrastructure, and capacity building in under-resourced areas. The findings underscore the need for globally coordinated, locally adapted strategies that center equity and resilience to ensure the realization of inclusive and quality education for all by 2030.